2014
DOI: 10.1007/s00056-014-0217-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of orthodontic measurements on dental plaster casts and 3D scans

Abstract: Inexperienced examiners, in particular, take measurements of mesiodistal tooth dimensions faster using a software-based method than when using a dental vernier caliper. Similar values were obtained with both methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 19 publications
5
21
1
8
Order By: Relevance
“…Additionally, the current results well confirm that measurements involving the premolars are more variable than the other ones [4]. In general, the overestimation of calliper measurements vs. digital casts data is in line with the literature reports [18], while the comparison with CBCT data is more scattered. For instance, on dry mandibles, most of CBCT measurements were significantly smaller than those obtained by using the calliper [6].…”
Section: Are Dental Measurements Taken On Plaster Casts Comparable Tosupporting
confidence: 81%
See 4 more Smart Citations
“…Additionally, the current results well confirm that measurements involving the premolars are more variable than the other ones [4]. In general, the overestimation of calliper measurements vs. digital casts data is in line with the literature reports [18], while the comparison with CBCT data is more scattered. For instance, on dry mandibles, most of CBCT measurements were significantly smaller than those obtained by using the calliper [6].…”
Section: Are Dental Measurements Taken On Plaster Casts Comparable Tosupporting
confidence: 81%
“…Literature is not in agreement about the technique with the best reproducibility: both digital models [4,5,7], and plaster models [16] had the best scores in different studies. Overall, only three mesiodistal crown diameters had differences larger than 0.5 mm, which is considered the threshold for clinical acceptability [7,18]. This corresponds to 8% of the analysed dental distances (3 out of 12 distances x 3 techniques values), a value larger than that reported by Tarazona-Álvarez et al [6] who found only 5% of significant differences when comparing 20 linear distances obtained directly on dried mandibles and on their CBCT scans.…”
Section: Are Dental Measurements Taken On Plaster Casts Comparable Tocontrasting
confidence: 44%
See 3 more Smart Citations